Integrated analysis of the expression profiles of the lncRNA-miRNA-mRNA ceRNA network in CASMCs under hypoxia and normoxia conditions in yak heart - Yang, Shanshan; Cui, Yan; Yu, Sijiu; He, Junfeng; Ma, Rui; Bai, Xuefeng; Zhang, Hui; Zhao, Pengfei (Scientific reports, 2025)
Hypoxia causes the occurrence of right heart hypertrophy and right heart failure. However, the yak living in the hypoxic environment, does not exhibit hypoxia-related pathological features. Therefore, It is of great significance to explore the hypoxia adaptation mechanism of yak heart. In this study, the yak heart coronary vascular smooth muscle cells (CASMCs) were treated with 21% O 2 (normoxic group) and 5% O 2 (hypoxic group). The results showed that hypoxia could promote the proliferation of CASMCs. Subsequently, we sequenced CASMCs in normoxic and hypoxic groups. The analysis revealed differential expression of 835 mRNAs, 285 lncRNAs and 126 miRNAs were between the two groups. GO and KEGG analysis showed that the differentially expressed genes were predominantly associated with extracellular matrix components, transcription factor activity, protein binding, immune system processes, metabolic processes and cell development processes and TGF-β, MAPK, cAMP, mTOR, PI3K-Akt and other signaling pathways. By constructing a network of mRNAs, miRNAs and lncRNAs based on the major differentially expressed RNAs, core regulatory elements associated with hypoxic adaptive function were identified. Our study may help to prove the potential role of differential genes related to hypoxic adaptation, and enhanced understanding of the molecular mechanisms of hypoxic adaptation in yak heart.